Cascade Reaction in Human Live Tissue Allows Clinically Applicable Diagnosis of Breast Cancer Morphology. Issue 2 (27th November 2018) - Tanei, Tomonori; Pradipta, Ambara R.; Morimoto, Koji; Fujii, Motoko; Arata, Mayumi; Ito, Akihiro; Yoshida, Minoru; Saigitbatalova, Elena; Kurbangalieva, Almira; Ikeda, Jun‐ichiro; Morii, Eiichi; Noguchi, Shinzaburo; et al.
Abstract: Clean operating margins in breast cancer surgery are important for preventing recurrence. However, the current methods for determining margins such as intraoperative frozen section analysis or imprint cytology are not satisfactory since they are time‐consuming and cause a burden on the patient and on hospitals with a limited accuracy. A "click‐to‐sense" probe is developed based on the detection of acrolein, which is a substance released by oxidatively stressed cancer cells and can be visualized under fluorescence microscopy. Using live breast tissues resected from breast cancer patients, it is demonstrated that this method can quickly, selectively, and sensitively differentiate cancer lesion from normal breast gland or benign proliferative lesions. Since acrolein is accumulated in all types of cancers, this method could be used to quickly assess the surgical margins in other types of cancer. Abstract : A "click‐to‐sense" acrolein probe allows the diagnosis of cancer morphology with high sensitivity and selectivity. The cancer lesion can be discriminated from normal breast gland by simply treating the live tissues from cancer patients with the "click‐to‐sense" acrolein probe.